1962
DOI: 10.1099/00221287-29-4-625
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Fate of Staphylococci after Phagocytosis

Abstract: SUMMARYFour methods were employed to study the immediate fate of staphylococci within leucocytes after phagocytosis. These were : ( a ) The met hod of Cohn & Morse where leucocytes and staphylococci were mixed in tubes and kept agitated. Periodically samples were removed and lightly centrifuged to sediment the leucocytes. Plate counts were made on the lysed leucocytes to measure the intracellular organisms, the supernatant to measure the extracellular population, and a non-centrifuged saniple to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Whether antibody is required for phagocytosis of S. aureus has also been brought into question in past studies. For example, early work by Shayegani and Kapral demonstrated that S. aureus can be ingested by leukocytes in the absence of antibodies under conditions now known to prime neutrophils for enhanced phagocytosis (17). Notably, adherence primes neutrophils for enhanced functions, such as phagocytosis, and the vast majority of community-associated S. aureus infections are those of skin and soft tissue—conditions under which phagocytes are adherent.…”
Section: Commentarymentioning
confidence: 99%
“…Whether antibody is required for phagocytosis of S. aureus has also been brought into question in past studies. For example, early work by Shayegani and Kapral demonstrated that S. aureus can be ingested by leukocytes in the absence of antibodies under conditions now known to prime neutrophils for enhanced phagocytosis (17). Notably, adherence primes neutrophils for enhanced functions, such as phagocytosis, and the vast majority of community-associated S. aureus infections are those of skin and soft tissue—conditions under which phagocytes are adherent.…”
Section: Commentarymentioning
confidence: 99%
“…Administration of the antigens alone seemed to have no effect on host resistance. Since S. aureus do not multiply within the cells (13,14) and are therefore eventually eliminated, the presence of homologous antigens is needed for stimulation of cellular resistance. This finding confirms a previous report (12) describing the need for elicitation in which cell-mediated immunity was tested at the cellular level, using peritoneal macrophages from infected and elicited animals in order to study the intracellular destruction of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…The tubes were placed in a roller drum (about 30 rev/min) in a 37 C incubator. The counts of viable total, and cell-associated staphylococci, staphylococci in the centrifugal supernatant fluid, and leukocytes were determined by methods described previously (3,13).…”
Section: Methodsmentioning
confidence: 99%
“…Coagulase-positive Staphylococcus aureus cells, after ingestion by both polymorphonuclear and mononuclear phagocytes, are more slowly and less completely rendered noncultivable than are other pyogenic cocci (1- 3,6,8,9,[11][12][13][14][15][16][17][18]). This relative refractoriness to intracellular killing in all probability is a significant factor in the tendency of staphylococcal infections to become chronic and recurrent.…”
mentioning
confidence: 99%